PENDEKATAN REVERSE ENGINEERING UNTUK PENGUJIAN KEAMANAN GUNA MENINGKATKAN KUALITAS PERANGKAT LUNAK - Muhammad Reza Redo (IIB Darmajaya, 2016)
A software development will take time and high cost. Reverse engineering is a technique or a way to find the principles of the technology of a product by analyzing the structure, function and how the product. By studying the structure of the functions of a product, this study aims to patching into software to improve the quality of the software itself. Patching which will be tested in this method is Checksum, Obfuscation / Obfuscated Code, API Redirection, Anti-Dumping where the results of the patching will be tested quality and the measured length of the Code, the Output File Results, and the number of changes that occur so as to increase the quality of the software itself Keywords : Reverse engineering, Patching, Checksum, Obfuscation / Obfuscated Code, API Redirection method, Anti Dumping Software